THE SPATIAL ANALYSIS OF KITE HOME INDUSTRY IN GROGOL VILLAGE, GROGOL SUB DISTRICT SUKOHARJO DISTRICT IN 2018 - Pramono, Aldino Itok; Rahman, MS Khabibur; Rifa’i, Muh. Husyain (Universitas Veteran Bangun Nusantara, 2019)
The research objective was to find out: (1) Distribution of kite industry homes, (2) social and economic conditions of kite craftsmen, (3) Factors of production and production that support the existence of kite home industries in Grogol Village, Grogol District Sukoharjo. The study used a spatial description data analysis method obtained from the Central Bureau of Statistics of Sukoharjo Regency and used questionnaire questionnaire and data calculation using the frequency table formula. The data contains data from interviews. Data collection techniques used are through interviews, observation and documentation. Data analysis techniques use spatial correlation. The results of the study are: (1) Distribution of kite industry home in 2018 which has a total of 20 industries (2) The social and economic conditions of kite craftsmen in Grogol Village in 2018 are quite good (3) Factors supporting the production of kites includes raw materials, business capital, labor, marketing, and industrial locations.